2011
DOI: 10.1097/hcr.0b013e318211e3ed
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of Aerobic Capacity With the Bruce Treadmill Protocol in Patients Being Assessed for Suspected Myocardial Ischemia

Abstract: This study demonstrates that estimates of aerobic capacity are significantly higher than measured values and this difference may result in a significant underestimation of morbidity/mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…It has been shown that performing an exercise Protocol with frontal or lateral support can change metabolic demand and adaptation to the treadmill. This also occurs for the evaluated executing the protocol with free arms 17 .…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that performing an exercise Protocol with frontal or lateral support can change metabolic demand and adaptation to the treadmill. This also occurs for the evaluated executing the protocol with free arms 17 .…”
Section: Discussionmentioning
confidence: 86%
“…For example, in treadmill studies investigating the effect of handrail support, a practice that lengthens treadmill time, VO 2peak is over-predicted by 20% to 30% [913,17] which would lead to a potentially false prognostic classification of CRF. To correct for the consistently observed over-prediction of VO 2peak of around 20% resulting from the use of handrail support, Foster has developed simple modifications of the ACSM equations for use when handrail support is observed during treadmill testing [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors may contribute to the error of TM-VO 2pred . They include 1) treadmill handrail support [913], 2) failure to use population specific equations [14–18], 3) inappropriate testing protocol [1921], 4) delayed oxygen kinetics [2224], 5) reproducibility of cardiopulmonary parameters [25,26], 6) altered mechanical efficiency with treadmill walking [27] and 7) lack of treadmill calibration [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Peak estimated METs achieved during maximal exercise testing are used to risk-stratify patients, prescribe individual exercise intensities for exercise training, and to determine changes in CRF following exercise interventions (ACPICR 2015). However, estimates of functional capacity may not accurately quantify VO 2peak , particularly during treadmill protocols (Myers et al, 1991;Milani et al, 1995;Pinkstaff et al, 2011). Whilst the limitations of estimating VO 2peak from a single exercise test are known, the accuracy of estimated changes in VO 2peak following an exercise training intervention is unclear.…”
Section: Introductionmentioning
confidence: 99%